Organisational perception of employee turnover - Linhartová, Lucie (Univerzita Pardubice, 2011)
Employee turnover is considered as one of the persisting problems of human resource management. This paper explores perception of employee turnover and related issues by managers. The data for this study were collected by three successive surveys. Two of surveys were focused on employees and causes of their disaffection and turnover and following third research was focused on managers. The aim is to identify causes of employee turnover, compare the results of surveys focused on employees and managers and suggest intervention into parts which were identified as controversial. Data were tested by statistical tests and analyses. Results show low usage of information regarding employee turnover among Czech managers. Based on the outputs of analyses it is possible to conclude that turnover is not usually managed in referred organisations and effort to objectively solve negative employee turnover have minimum of referred managers. Intervention to the system of turnover management is suggested with greater emphasis of top management to existing practices, which are very often ignored by the line managers. The findings stimulate changes inside organisations to lower turnover, because even a minimum positive change of conditions bring greater effect than invested effort and costs.
Keywords: turnover; human resources; managers; organisation; fluctuation